Regional Comprehensive Economic Partnership and European Union in Asia – India as Regional Determinant? - Narayanan Raviprasad (Studia Ekonomiczne i Regionalne)
Inner dynamics influence external processes of economic interaction between nations, trading blocs, and multilateral institutions. The flexibility and internal cohesion of domestic decision-making mechanisms creates conditions of forging ahead or adoption of stasis as reflex position during negotiations. The research article seeks to explain the policy making and reflex postures of India towards trade negotiations while seeking economic alliances to further commercial prosperity for the world’s largest democracy in population terms with the European Union. The inherent dynamism comes forward in economic policy making, exemplified by multiple channels and influences leading to fruition of acknowledging benefits over inertia.